Laser directed energy deposition additive manufacturing of Al7075 alloy: Process development, microstructure, and porosity - Wenjing Ren; Lianyong Xu; Chao Qin; Yongdian Han; Lei Zhao; Kangda Hao (Journal of Materials Research and Technology, 2024)
7xxx series aluminum alloys are priority materials adopted in aerospace because of their lightweight property and excellent mechanical performance. The combination of lightweight material and additive manufacturing techniques can significantly promote lightweight design in many industries. This study developed the optimal process for manufacturing Al7075 alloy by laser-aided directed energy deposition and revealed the material properties of the as-deposited Al7075 specimens. Firstly, single-track experiments were conducted by varying laser power, printing speed, and powder delivery rate in broad ranges. Results indicated that the printing speed and powder delivery rate impact the surface finish and shape of single-track beads considerably. Block specimens printed with the optimal parameters selected from the single-track experiments present crack-free quality and have a high relative density of up to 99.89%. Second phases with rich Cu, Mg, and Zn elements along the inter-dendritic regions and grain boundaries were observed from the microstructure inspection. The composition of zinc in the deposited samples is lower than usual, which leads to a relatively low microhardness.